Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1093/ejo/cjn037
|View full text |Cite
|
Sign up to set email alerts
|

The use of a neodymium-iron-boron magnet device for positioning a multi-stranded wire retainer in lingual retention--a pilot study in humans

Abstract: The aim of this study was to evaluate the time requirement of a newly developed device made of neodymium-iron-boron (NdFeB) magnets for positioning a multi-stranded, canine-to-canine retainer during bonding compared with dental floss and a transfer tray. Forty-five patients aged between 12 and 33 years (26 male, 19 female) previously treated with fixed appliances were enrolled in the study. The patients were randomly allocated to three groups (15 per group). For each group a mandibular canine-to-canine retaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
0
9
0
3
Order By: Relevance
“…In a clinical study with 45 patients [8], the investigators demonstrated that retainers were significantly more rapidly fixed with the magnet chain than with dental floss or with a custommade resin-positioning aid as used in this study. As the time for adhesive fixation is reduced, there is less probability that the etched enamel surface will be contaminated with saliva, sulcus fluid, or blood, possibly increasing the retainer stability [1,6].…”
Section: Diskussionmentioning
confidence: 73%
See 3 more Smart Citations
“…In a clinical study with 45 patients [8], the investigators demonstrated that retainers were significantly more rapidly fixed with the magnet chain than with dental floss or with a custommade resin-positioning aid as used in this study. As the time for adhesive fixation is reduced, there is less probability that the etched enamel surface will be contaminated with saliva, sulcus fluid, or blood, possibly increasing the retainer stability [1,6].…”
Section: Diskussionmentioning
confidence: 73%
“…The slightly better fit only indicates that the lack of positioning with the magnet chain is ultimately not a problem and that the aforementioned clinical advantages [8] are not accompanied by inferior fit. The magnet chain method is also generally less expensive, as it dispenses with various laboratory steps necessary to make a positioning aid.…”
Section: Interessenkonfliktmentioning
confidence: 97%
See 2 more Smart Citations
“…Büküm işlemi model üzerinde gerçekleştirilen retainerlar hasta ağzına uyumlanırken dişler üzerinde pasif olarak sabit kalabilmesi için kullanılan farklı yön-temler mevcuttur. Bunlar [45][46][47][48][49][50][51][52][53] (Resim 2); parmak yardımı ile sabit tutmak, dental floss, elastik ligatürler, ligatür telleri ile sabitlemek, ortodontik mumların kullanımı, springlerin kullanımı ile sabitleme, ortodontik elastik zincir, ortodontik separatörler ile sabitleme, magnetler kullanılarak sabitleme, ağız içine taşıyıcı ajanlar(heavy body...) dır.…”
Section: -Esnek Tellerden Yapılan Sabit Lingualunclassified